PyDESeq2: a python package for bulk RNA-seq differential expression analysis - Muzellec, Boris; Teleńczuk, Maria; Cabeli, Vincent; Andreux, Mathieu (Bioinformatics (Oxford, England), 2023)
Abstract Summary We present PyDESeq2, a python implementation of the DESeq2 workflow for differential expression analysis on bulk RNA-seq data. This re-implementation yields similar, but not identical, results: it achieves higher model likelihood, allows speed improvements on large datasets, as shown in experiments on TCGA data, and can be more easily interfaced with modern python-based data science tools. Availability and Implementation PyDESeq2 is released as an open-source software under the MIT license. The source code is available on GitHub at https://github.com/owkin/PyDESeq2 and documented at https://pydeseq2.readthedocs.io. PyDESeq2 is part of the scverse ecosystem.